2015
DOI: 10.1371/journal.pone.0135199
|View full text |Cite
|
Sign up to set email alerts
|

Using the Electronic Nose to Identify Airway Infection during COPD Exacerbations

Abstract: BackgroundThe electronic nose (e-nose) detects volatile organic compounds (VOCs) in exhaled air. We hypothesized that the exhaled VOCs print is different in stable vs. exacerbated patients with chronic obstructive pulmonary disease (COPD), particularly if the latter is associated with airway bacterial infection, and that the e-nose can distinguish them.MethodsSmell-prints of the bacteria most commonly involved in exacerbations of COPD (ECOPD) were identified in vitro. Subsequently, we tested our hypothesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 44 publications
3
54
0
Order By: Relevance
“…[118] It also discriminated the VOCs from patients with pneumonia, from the VOCs of healthy controls, with 100% accuracy. [119] Finally, the same device allowed to identify the bacterial species in 72% of patients affected with sinusitis. [120] A prospective cross sectional proof-of-concept study was performed for the GC-IMS E-nose in the analysis of VOCs from exhaled breath from patients and to distinguish bacterial from viral respiratory tract infections.…”
Section: Electronic Nosementioning
confidence: 99%
See 1 more Smart Citation
“…[118] It also discriminated the VOCs from patients with pneumonia, from the VOCs of healthy controls, with 100% accuracy. [119] Finally, the same device allowed to identify the bacterial species in 72% of patients affected with sinusitis. [120] A prospective cross sectional proof-of-concept study was performed for the GC-IMS E-nose in the analysis of VOCs from exhaled breath from patients and to distinguish bacterial from viral respiratory tract infections.…”
Section: Electronic Nosementioning
confidence: 99%
“…Selected examples of future technologies for pathogen identification (ID) and antimicrobial susceptibility testing (AST). No CA A [114,119,[121][122][123][124] Flow cytometry Follow the viability of microorganisms, after exposure to antibiotics using dyes that do not permeate the cell walls of healthy bacteria 2-3 h No Yes POP A [140,141] IMC (isothermal microcalorimetry)…”
Section: Electronic Nosementioning
confidence: 99%
“…Exclusions were: patients with age less than 18 years; unable to give informed consent or with other respiratory diseases such as CF, active allergic bronchopulmonary aspergillosis, active non-tuberculous mycobacterial infection or pulmonary fibrosis with traction bronchiectasis, as well as patients receiving immunoglobulin replacement therapy or chronic systemic corticosteroid treatment. Sample size was calculated as described in previous studies [17,18].…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, several studies have shown that the e-nose is also able to detect respiratory infections. In COPD, the e-nose has successfully distinguished patients with and without airway bacterial infection during clinical stability [17] and acute exacerbations [18]. Some studies have suggested that specific bacteria such as P. aeruginosa, may produce distinguishable VOC [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The Cyranose 320 and E50835 electronic nose devices have been utilized to differentiate between P. aeruginosa, S. aureus, and E. coli isolates based on VOC patterns from the headspace. 81,[111][112][113] However, it does not provide details regarding the individual volatile compounds emitted by the bacteria.…”
Section: Electronic Nosementioning
confidence: 99%